Agricultural Financing and Economic Growth: A Bayesian VAR Examination of the Nigerian Evidence - Achumu, James; Ezirim, Ucheoma I.; Ezirm, Chinedu B.; Chekwa, Charles (Journal of Applied Business and Economics, 2022)
The study attempted to investigate the effects of agricultural financing by both the government and the private sector banks on the gross domestic product of Nigeria, using the Bayesian VAR methodology against annual data from 1981 to 2019. The results indicate that the agriculture credit guarantee scheme funding significantly and positively affects the aggregate national output of Nigeria. The non-governmentguaranteed direct loans and advances from the banks to the agricultural sector significantly and positively affect the aggregate national output of Nigeria. The real contribution of direct government expenditures on the agriculture sector to the gross domestic product is positive, but not significant. The recommendations favor the continuation and strengthening of the ACG Scheme and the encouragement of the relevant development and commercial banks by government and the Central Bank of Nigeria to increase lending to the agricultural sector through moral suasion and deliberate policy.